2018
DOI: 10.2147/dddt.s181798
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effects of traditional Chinese medicine Fusu agent in LPS-induced acute lung injury model rats

Abstract: PurposeAcute lung injury (ALI) is a common and fatal oxidative stress in the lung, mainly induced by endothelial injury and capillary leakage. In our previous study, “Fusu agent”, a traditional Chinese medicine, was found to exert preventive effect on endothelial damage in lipopoly-saccharide (LPS)-induced ALI model rats partially via inhibiting heparanase1 (HPA1) activation and inhibiting the inflammatory factors. However, it is still unknown whether Fusu agent exerts its therapeutic effect in LPS-induced ALI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Numerous studies have shown that it plays a key role in ALI [40]. In ALI, LPS also induces the formation of inflammatory mediators through the NF-κB pathway [41,42]. In resting state, IκBα and NF-κB p65, p50 exist in inactivation state.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that it plays a key role in ALI [40]. In ALI, LPS also induces the formation of inflammatory mediators through the NF-κB pathway [41,42]. In resting state, IκBα and NF-κB p65, p50 exist in inactivation state.…”
Section: Discussionmentioning
confidence: 99%
“…The mice had free access to standard diet and water. The acute lung injury mouse model was established according to the method previously published [ 20 , 21 ], with some modifications. Briefly, the ALI mouse model the established via nasal administration of 25 mg/kg LPS (Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial transmembrane potential stabilization and decrease of lactate dehydrogenase leakage. [ 38 ] Carotenoid Crocin LPS-induced acute respiratory distress syndrome in mice and LPS-induced inflammation in HUVEC In vivo and vitro Mice were pretreated with crocin at 15, 30 and 60 mg/kg. After 7 h, ARDS was induced in mice using intravenous LPS (20 mg/kg) administration for 6 h. HUVEC were pretreated with crocin at 20 μM for 1 h following inflammation with LPS at 1 μg/mL during 6 h. Improvement of pulmonary vascular permeability.…”
Section: Pharmaceutical Active Natural Products With Potential To Trementioning
confidence: 99%